Tips Menjadi Guru yang Bersinar pada Masa Depan - Husin, M. Said (Dinamika Ilmu, 2010)
This article provides a number of simple educational ideas promoted to enhance some core competences of a Madrasah teacher which can be reached by two terms of strategies : short term and long term strategies. The short term covers five aspects. The first aspect which is defined as fundamental discusses the way how a Madrasah teacher perceives his/her teaching profession, colleagues, students, and issues on education. Having able to rethink these domains will lead him or her know his or her positive and negative sides. Such understanding of both sides should force him/her to have a strong commitment to enrich the positive side, on one hand, and to diminish the negative one, on the other hand. Then, a Madrasah teacher needs to reflect this commitment in his or her individual competence to carry on learning and improving his or her technical capacity in instruction. This may be one of the corner stones to develop himself or herself to be able to implement the assignment responsibly. The capacity as a professional teacher may also bring him or her to be well-informed figure whom people around him or her will become to be enlightened. Next, this professional teacher should not also set up in one or more comfort zones, such as typical system and culture of organization, which make him or her enjoy the life as it is, he or she is required to open his or her mind to look for new, more and other challenging comfort zones in accordance with his or her future career. After that, he or she should consider and internalize wisely ethical values which are called as Islamic professional ethics as his or her spirit to carry out his or her job. Finally, this distinguished post should listen to his or her deepest voice of heart as well. These voices are about to put as his or her inspiring component to be acted as effective as possible. The long term strategy, however, merely emphasizes on one single aspect, that is the importance of educational and training services. Once a madrasah teacher has a paralleled background of study he or she may already have one valuable point. His or her other capacity will be easily explored and served through a series of appropriate trainings. The trainings are academically considered to be an additional mean for his or her outshined career.